Proposal for the Size of the Fleet to Provide Winter Road Maintenance - Miroslav Gabor (Communications - Scientific letters of the University of Zilina, 2010)
The article describes an optimisation model which was used to create the operation plan of winter road maintenance [6]. The model takes into consideration a number of factors of road description, such as road network topology, road categories and level of services. They result in suggesting the necessary number of vehicles the centres of winter road maintenance should have to be able to keep, the servicing time limit given by the operation plan in case of a calamity. The model also proposes what the most optimal vehicle routing would be timewise.